The Role of Brand Trust in Determining The Relationship Between Brand Affection and Loyalty Programs on Customer Loyalty - Jojor Marintan Silalahi; Lizar Alfansi; Akram Harmoni Wiardi (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2016)
study investigates how brand affection, loyalty programs, and brand trust determine the loyalty in airways industry. We examined the influence of brand trust and brand affection on loyalty in airlines services. The airways companies applied loyalty programs as a trend. The purpose of the loyalty programs is to encourage the loyalty of the customers. The purpose of this study is to analyze the influence of brand affection and loyalty programs on brand trust and loyalty among GarudaMiles members. Primary data were collected through a survey. Data collected by online quistionnaire through social media and resulting 171 processable questionnaire. Data were analysed using confirmatory factor analysis and structural equation modelling. Confirmatory factor analysis within structural equation modeling were carried out to assess adequacy of the measurements and validity of the model. We found that brand affection is not significantly influence customer loyalty; brand affection significantly influence brand trust; and brand trust significantly influence customer loyalty. This result indicate that brand affection has an indirrect effect on loyalty, it’s mediated by brand trust. Loyalty program is not significantly effect brand trust, it has direct effect on loyalty. It’s become clear that only brand trust mediates the relationship of brand affection and loyalty. The customers of the airways companies tend to be loyal because of the loyalty programs applied by the airways companies. These finding add performance effectiveness and long-term relationships with customers in airlines industry to the factors needed to respond to the highly competitive situation at present, which will be even more important with the ASEAN Economic Community in 2015.Keywords: Brand Affection, Brand Trust, loyalty, Loyalty Program